The Impact of Prison Overcrowding on the Rights and Well-being of Inmates in Indonesia: A Legal Perspective - Irma Nurul Tyana; Marisa Kurnianingsih (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2025)
Overcrowding in detention centers remains a critical issue within Indonesia's criminal justice system, particularly due to its detrimental impact on the fulfillment of prisoners' basic rights. This study aims to examine how the rights of inmates are upheld at the Class IIB Boyolali Penitentiary under overcrowded conditions and to identify the key obstacles encountered in the process. Employing an empirical juridical method with a qualitative approach, the research was conducted through interviews, observations, and the analysis of relevant legal documents. The findings reveal that, despite the overcrowded environment, efforts are still made to uphold fundamental prisoner rights, including access to healthcare, adequate nutrition, religious practices, legal aid, and family communication. However, the fulfillment of these rights is hindered by limitations in infrastructure, budget, and human resources. The study concludes that enhancing the effectiveness of alternative sentencing policies and improving prison management systems are essential to ensuring the optimal protection of prisoners' rights.